2022
DOI: 10.46676/ij-fanres.v3i3.113
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological quality of commercial fresh and frozen chicken drumstick in Umuhia, Nigeria

Abstract: Chicken meat, an excellent source of good quality proteins, is highly susceptible to microbial contaminations and heavy metals from feeds, processing, and retailing environments, thereby posing health risks to consumers. Therefore, the proximate composition, heavy metal concentrations, and microbial loads of commercial fresh and frozen chicken drumsticks, randomly sourced from poultry farms and groceries, respectively, within Umuahia metropolis, Abia State, Nigeria, were investigated to ascertain their qualiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…When assessing the degree of microbial contamination in foods, the total bacterial count is an important factor that should be taken into consideration (Hafez et al, 2019). The obtained total coliform count were less than 10 2 cfu/ g, signifying their safety for human consumption, as the International Commission on Microbiological Specifications of Foods (ICMSF) stated that the acceptable level of the total coliforms (TC) for raw chicken meat is ≤ 10 2 cfu/ g (Okolo et al, 2022). Concerning Salmonella sp., which is the most significant bacterial pathogen in the chicken meat that can cause several foodborne illness; however, no Salmonella was currently detected in all the treated samples.…”
Section: Discussionmentioning
confidence: 96%
“…When assessing the degree of microbial contamination in foods, the total bacterial count is an important factor that should be taken into consideration (Hafez et al, 2019). The obtained total coliform count were less than 10 2 cfu/ g, signifying their safety for human consumption, as the International Commission on Microbiological Specifications of Foods (ICMSF) stated that the acceptable level of the total coliforms (TC) for raw chicken meat is ≤ 10 2 cfu/ g (Okolo et al, 2022). Concerning Salmonella sp., which is the most significant bacterial pathogen in the chicken meat that can cause several foodborne illness; however, no Salmonella was currently detected in all the treated samples.…”
Section: Discussionmentioning
confidence: 96%
“…Chicken manure can be characterized by its low C/N ratio, high moisture content, low porosity, and high pH. The addition of sawdust, wood chips and rice husk enhance the C/N ratio and porosity while minimizing the moisture level [15], [16]. It has been observed that co-composting biochar with organic matter accelerates composting and produces a substrate with higher fertility and carbon sequestration capability [17].…”
Section: B Compostingmentioning
confidence: 99%
“…The feeds, water samples, and broilers were randomly sampled from poultry farms along Abak, Aka, Nwanaiba, and Oron Roads within Uyo Metropolis following the methods of Okolo et al (2022). At each of the poultry farms, five hundred grams each of starter and finisher feeds were collected in polyethylene bags.…”
Section: Sample Collection and Treatmentmentioning
confidence: 99%